Transgenic retinoic acid sensor lines in zebrafish indicate regions of available embryonic retinoic acid. Issue 8 (18th June 2013) - Mandal, Amrita; Rydeen, Ariel; Anderson, Jane; Sorrell, Mollie R.J.; Zygmunt, Tomas; Torres‐Vázquez, Jesús; Waxman, Joshua S.
ABSTRACT Background: Retinoic acid (RA) signaling plays a critical role in vertebrate development. Transcriptional reporters of RA signaling in zebrafish, thus far, have not reflected the broader availability of embryonic RA, necessitating additional tools to enhance our understanding of the spatial and temporal activity of RA signaling in vivo. Results: We have generated novel transgenic RA sensors in which a RA receptor (RAR) ligand‐binding domain (RLBD) is fused to the Gal4 DNA‐binding domain (GDBD) or a VP16‐GDBD (VPBD) construct. Stable transgenic lines expressing these proteins when crossed with UAS reporter lines are responsive to RA. Interestingly, the VPBD RA sensor is significantly more sensitive than the GDBD sensor and demonstrates there may be almost ubiquitous availability of RA within the early embryo. Using confocal microscopy to compare the expression of the GDBD RA sensor to our previously established RA signaling transcriptional reporter line, Tg(12XRARE:EGFP), illustrates these reporters have significant overlap, but that expression from the RA sensor is much broader. We also identify previously unreported domains of expression for the Tg(12XRARE:EGFP) line. Conclusions: Our novel RA sensor lines will be useful and complementary tools for studying RA signaling during development and anatomical structures independent of RA signaling. Developmental Dynamics 242:989–1000, 2013. © 2013 Wiley Periodicals, Inc.